(3JGQjN eOjfI OeTbs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s ((3eSLO bdhS (B_ (3OeTb s)
(3ChdgG (B:s
(3Chd GdehLhO efgG CKfGA JQLeI YHO Gddg Hf HTQ GdeGRfi , bhdg (B: (3CNHQfG CHh HcQ Hf GdYHGS Cf CMeO Hf efUhQ bGd (B: (3SeYJ eSde Hf GdMLGL jbhd (B: (3CHh UahGf YHO Gddg Hf HTQ GdeGRfi s
(3BNQgG (B:s
(3JfJgi HJQLeI YHO Gddg Hf YHGS Hf YHO GdeWdH , hBNQgG bhdg (B: (3CNHQfG CHh GdbGSe Hf GdSeQbfOi Yf YeQh Hf OjfGQ Yf GHf YHGS bGd (B: (3Chd GdJGQjN ai GdSfI GdJi bOe ajgG QShd Gddg Udi Gddg Ydjg hSde hajgG hdO GHf YHGS BNQ GdLRA GdSGHY hGdNeSjf HYOs
(3CYXe JhGQjN OeTbs
(3GdeLdO GdSGHY (B: (3hjJVef GdC(B<(3RGA CKfGA GdLRA (B242 _ (3BNQ GdLRA (B257s
(3ai OGNdgG hBNQgG UhQ SeGYGJ Ydi GdeDda ai OeTb CbOegG HJGQjN (B562(3g`s
(3fbdgG GdHQRGdi eNJUQI ef GdCUd GdJi fbd efgG fSNJg gPg s
(3hHBNQgG EWdGY Ydi GHf UGM MUf cjaGSfI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs